2017
DOI: 10.1002/2016ja023372
|View full text |Cite
|
Sign up to set email alerts
|

Propagation characteristics of plasmaspheric hiss: Van Allen Probe observations and global empirical models

Abstract: Based on the Van Allen Probe A observations from 1 October 2012 to 31 December 2014, we develop two empirical models to respectively describe the hiss wave normal angle (WNA) and amplitude variations in the Earth's plasmasphere for different substorm activities. The long‐term observations indicate that the plasmaspheric hiss amplitudes on the dayside increase when substorm activity is enhanced (AE index increases), and the dayside hiss amplitudes are greater than the nightside. However, the propagation angles … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
82
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 51 publications
(95 citation statements)
references
References 37 publications
11
82
1
1
Order By: Relevance
“…The wave normal angle (WNA) and polarization ellipticity (Figures c–d) derived from the singular value decomposition (SVD) method (Santolík et al, ) indicate that these emissions are nearly perpendicularly propagating and linearly polarized. These wave properties confirm that the amplified emissions are magnetosonic waves (Yu J et al, ).…”
Section: Observations Of Low‐frequency Ms Wavessupporting
confidence: 78%
See 1 more Smart Citation
“…The wave normal angle (WNA) and polarization ellipticity (Figures c–d) derived from the singular value decomposition (SVD) method (Santolík et al, ) indicate that these emissions are nearly perpendicularly propagating and linearly polarized. These wave properties confirm that the amplified emissions are magnetosonic waves (Yu J et al, ).…”
Section: Observations Of Low‐frequency Ms Wavessupporting
confidence: 78%
“…Magnetosonic (MS) waves, also known as equatorial noise, are predominantly observed near the magnetic equator at frequencies between the proton cyclotron frequency ( f cp ) and the lower hybrid resonance frequency ( f LHR ) both inside and outside the plasmasphere (Russell et al, ; Perraut et al, ; Santolík et al, ; Meredith et al, ; Fu HS et al, ; Posch et al, ; Li LY et al, , b; Yuan ZG et al, ; Liu X et al, ; Liu B et al, ). These waves are mostly linearly polarized; they propagate nearly perpendicular to the background magnetic field (Zhima et al, ; Yu J et al, ; Su ZP et al, ), and they are believed to be excited by proton ring distributions (Horne et al, ; Chen LJ et al, , ; Liu KJ et al, ; Xiao FL et al, ). Recently, MS waves have caught much attention because, by resonating with particles, they play a crucial role in radiation belt dynamics.…”
Section: Introductionmentioning
confidence: 99%
“…The PP position ( L pp ) is roughly marked out by the red vertical line in Figures c–h. Inside the plasmasphere ( L < L pp ), there is plasmaspheric hiss whose frequency ( f ) is above the lower hybrid resonance frequency ( f LHR ) (Li et al, ; Yu et al, , ). However, the power spectral density of electric field from the high‐frequency receiver indicates that there is no electrostatic electron cyclotron harmonic waves inside the plasmapause ( L < L pp ).…”
Section: Van Allen Probe Observations and Numerical Validationmentioning
confidence: 99%
“…Falkowski et al () studying dayside sector plasmaspheric hiss found that the waves were associated with both substorms and solar wind pressure pulses (for solar wind pressure effects, see also Gail & Inan, ; Kokubun, ; Shinbori et al, ; Tsurutani et al, , ; Remya et al, ; Yue et al, ). The substorm‐dependent scenario is that substorm‐injected electrons gradient drift from their midnight sector injection to the dayside magnetosphere, generate chorus there (Meredith et al, ; Tsurutani & Smith, , ), and the waves then propagate into the plasmasphere (Bortnik et al, ; Bortnik, Li, et al, ; Bortnik, Thorne, et al, ; Breneman et al, ; L. Chen et al, ; Li et al, ; Li, Chen, et al, ; Santolik, ; Santolik & Chum, ; Thorne et al, , ; Tsurutani et al, ).…”
Section: Introductionmentioning
confidence: 99%